(untitled) (Papeles, 2022)
English learning in general and speaking skill development are demanded as a quality in the graduated senior high school student profile. During the development of speaking skill in a foreign language (English), it is important for the student to recognize their strengths and weaknesses. Corrective Feedback (CF) favors the development of oral skills. The objective of this qualitative study was to illustrate the practices of teachers regarding feedback in the speaking skill of a foreign language during the classes taught remotely, the moments in which they do it and their results in the orality of the students at the high school in synchronous classes. The research questions were: What CF strategies are applied in students speaking skill from the teaching perspective during the synchronous online classes? When do teachers correct the speaking production in synchronous online classes? and What are the results that teachers observe in the speaking of students in the foreign language from CF? The results showed that the explicit CF, reformulation, and metalinguistic strategies were used. Most of the participants (80 %) used delayed feedback. In addition, teachers observe that CF favors the development of oral skills of students in the long term. It is concluded that the use of CF strategies is limited and varies according to the context, the students’ needs and the learning objective.